A revised petrological model for subducted oceanic crust: insights from phase equilibrium modelling - Hernández‐Uribe, D; Palin, R (Wiley, 2019)
Many geological and geodynamical studies of metamorphism in subduction zones have relied upon worldwide compilations of modelled slab‐top pressure–temperature (P–T) conditions, although recent evaluation of such data sets suggests that these predictions are ~100–300°C colder at any given pressure than the conditions recorded by exhumed metamorphic rocks. As such, geochemical, petrological and geophysical interpretations formulated using such ‘cold’ assumptions may be subject to error and uncertainty. Here, we apply thermodynamic phase equilibrium calculations to forward‐model how phase assemblages, the P–T conditions of key devolatilization reactions and the effect of densification with depth vary for typical mid‐ocean ridge basalt (MORB) along these newly defined ‘hotter’ subduction zone geotherms for cold, warm and average environments. The depth and extent of devolatilization of MORB is strongly dependent on the geotherm along which the oceanic crust subducts. At the onset of subduction along a warm geotherm, metabasites contain ~3 wt% H2O and release ~45% of this fluid in a single pulse at ~20 km, correlating with chlorite and epidote breakdown. Below these depths, metamorphosed MORB will dehydrate incrementally due to gradual amphibole breakdown, becoming almost completely dehydrated at ~70 km. Oceanic crust subducting along an average geotherm will contain ~3.5 wt% of H2O at the onset of subduction and will release ~40% of the bulk‐rock H2O in two fluid pluses occurring at ~30 and 50 km, correlating with chlorite breakdown. Below these depths, gradual dehydration of ~50% of the bulk‐rock H2O due to amphibole breakdown leads to near‐complete dehydration at ~80 km. By contrast, in cold subduction zones, metamorphosed MORB will typically be H2O‐undersaturated and will dehydrate gradually at different depths, transporting ~0.6 wt% H2O to sub‐arc depths. As the volume of fluid released via these dehydration reactions differs strongly between cold, average and warm scenarios, different degrees of serpentinization of the mantle forearc are expected worldwide and thus, the efficacy of buoyancy‐driven exhumation should vary strongly in space and time. Metabasites subducting along a warm and average geotherm will liberate most of the fluids at shallower depths, suggesting that these lithologies might preferentially exhume, yet MORB subducting along cold geotherms will not dehydrate until greater depths, inhibiting its return to the surface. Critically, while we show that metabasites formed along warmer geotherms are denser than metabasites from colder geotherms at any equivalent depth, buoyancy‐driven exhumation provoked by fluids plays a notably more important role in exhumation potential than the overall bulk‐rock ‘metamorphic’ density. Furthermore, we show that lawsonite does not stabilize in average and warmer subduction zones, which provides a simple but important solution to the mismatch between its predicted abundance in experiments and its rarity in nature and argues against its use as a reliable petrogenetic indicator of subduction throughout deep geological time, as has been suggested by some recent studies.